2021
DOI: 10.1111/pce.14220
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal density in Pinus sylvestris as an indicator of temperature rather than CO2: Evidence from a pan‐European transect

Abstract: The commonly observed negative relationship between stomatal density (SD) and atmospheric CO2 has led to SD being proposed as an indicator of atmospheric CO2 concentration. The use of SD as a proxy for CO2, however, has been hampered by an insufficient understanding of the intraspecific variation of this trait. We hypothesized that SD in Pinus sylvestris, a widely distributed conifer, varies geographically and that this variation is determined by major climatic variables. By sampling needles from naturally gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…Stomatal density was the main leaf hydraulic trait associated with climate-related population differentiation in both of our study species. In E. ovata it was related to home-site temperature, consistent with reports for other tree [ 97 ] and shrub [ 103 ] species. Population mean stomatal density was positively correlated with stomatal length per unit leaf area and vein density, consistent with coordinated water transport, with both traits affecting the maximum rates of photosynthesis and water loss [ 104 , 105 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Stomatal density was the main leaf hydraulic trait associated with climate-related population differentiation in both of our study species. In E. ovata it was related to home-site temperature, consistent with reports for other tree [ 97 ] and shrub [ 103 ] species. Population mean stomatal density was positively correlated with stomatal length per unit leaf area and vein density, consistent with coordinated water transport, with both traits affecting the maximum rates of photosynthesis and water loss [ 104 , 105 ].…”
Section: Discussionsupporting
confidence: 88%
“…While other recent large-scale, common-garden studies of population variation in forest tree species have shown intraspecific relationships between climate and hydraulic leaf traits [ 96 , 97 ], few common garden studies have investigated intraspecific variation in leaf hydraulic traits in eucalypt species with which to compare our results. However, population studies of associated physiological traits such as photosynthetic rate, stomatal conductance and surrogates of water use efficiency have reported varying degrees of genetic variation in these traits [ 35 , 43 , 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scotophases (ZT 0 & 6 h) experienced a higher melatonin increase than photophases (ZT 12 & 18 h).This has been demonstrated in many studies that the thermal degradation of melatonin is more rapid than photodegradation (Bellmaine et al 2020;Sadak and Ramadan 2021;Song et al 2022). Because the number of stomata in plants functioned as a proxy for temperature (Marek et al, 2022;Brewer et al 2022;Steinthorsdottir et al 2022), it was critical to investigate how melatonin influenced stomatal behaviour on both the adaxial and abaxial leaf surfaces. The stomata in P. oleracea were paracytic (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The underlying mechanism is shifting the balance in favour of CO 2 uptake by increasing it under water loss conditions. On the other hand, a recent study has also suggested that stomatal density may be equally or more affected by temperature, specifically the large continental-scale geographical variations with an interplay of precipitation [ 18 ].…”
Section: Water Relations Transpiration and Stomatal Conductancementioning
confidence: 99%